PERAN SISTEM INFORMASI MANAJEMEN DALAM PENERAPAN DATA MASKING UNTUK MENINGKATKAN KEAMANAN DATA RESI PADA E – COMMERCE - Rayyan Firdaus; Chayara Alima Qanita; Dini Aulia (CV. Denasya Smart Publisher, 2026)
The rapid growth of e-commerce has increased the volume of customer data, including sensitive shipping receipt data. However, data protection in this sector remains suboptimal, making the risk of personal data leakage a serious threat. This study aims to analyze the role of Management Information Systems (MIS) in supporting the implementation of data masking to improve the security of receipt data on e-commerce platforms. The method used is a literature study with a qualitative approach, reviewing various scientific sources published between 2021 and 2026. The results show that MIS plays an important role in three main aspects: RBAC-based access restrictions, AI/NLP-based sensitive data sorting, and dynamic data masking on the interface without altering the original data. In addition, MIS also maintains smooth post-masking operations by maintaining the data format. The implementation of MIS-based data masking has proven effective in improving receipt data security, as demonstrated in previous research. Thus, MIS and data masking are strategic, complementary solutions in protecting customer privacy in the digital era.